Multicultural Education and Community Economic Systems in Indonesia PAI Perspective - Muhammad Ilyas; St. Wardah Hanafie Das (Universitas Muhammadiyah Palu, 2025)
This paper explores the integration of multicultural education and community-based economic systems in Indonesia from the perspective of Pendidikan Agama Islam (PAI). Multicultural education in Indonesia is a crucial approach to fostering mutual respect and understanding among the diverse ethnic and religious groups in the country. Simultaneously, the economic system known as 'Sistem Ekonomi Kerakyatan', or people's economy, emphasizes equity and communal prosperity in line with Islamic economic principles. This study analyzes how PAI can inform and enhance both these frameworks to promote inclusive educational practices and economic systems that cater to diverse communities. By employing qualitative methods, including literature review and case studies, the paper demonstrates the potential of PAI to serve as a foundational element in strengthening societal cohesion and economic sustainability. The findings suggest that a PAI-informed approach can effectively address the challenges of diversity and economic disparity, offering a model for other nations with similar multicultural and economic contexts.